Changes in erosion processes and morphology of step-pool channels in the ski resort with artificial snowmaking, an example from Gubałowskie foothills - Piątek, Dawid; Gołąb, Agata; Wrońska-Wałach, Dominika (Quaestiones Geographicae, 2025)
The construction of ski runs with artificial snowmaking in mountainous areas changes natural water circulation and leads to the activation of erosion and deposition processes. To recognise this relationship, we selected a small catchment in the Gubałowskie Foothills, the Inner Carpathians, where 17% of the area is covered by the ski runs. In our study, we hypostatised that: (i) channels draining ski runs exhibit different morphological and morphometric characteristics compared to those that do not drain ski runs; (ii) the statistical relationships between channel morphometric parameters differ between impacted and non-impacted channels; and (iii) erosion and deposition processes lead to measurable changes in channel morphology that can be quantitatively assessed in the research area. To identify these changes, we conducted geomorphological mapping of step-pool channels, statistical analyses, digital elevation model (DEM), and DEM of difference (DoD) analyses (based on point clouds from 2016 to 2023). To identify the effect of ski run construction on channel morphology, we divided channels into two groups: (1) stream channels unaffected by ski infrastructure and (2) stream channels affected by ski infrastructure. Results showed that the routing of drainage from the ski runs to the channels leads to a significant erosion in the channels with the maximum deepening, up to 2.6 m. It also changes the dominant geomorphological processes in the channels. Fluvial processes are beginning to dominate slope processes. The described changes occurred already 8 years after the opening of the ski station and revealed environmental degradation connected to artificial snowmaking in ski resorts.